School is not "place for belly" - Denise Raquel Rohr; Maria Simone Vione Schwengber (Universidade Federal de Santa Maria, 2015)
Public schools and teenage pregnancy were the focus of the master's dissertation School experiences of mother-girls from the suburbs of Ijui-RS. In this study, the relationship between public schools and pregnant students or teenage mothers is discussed, from the speech of management teams about the actions tried at schools facing issues of sexuality and pregnancy. It is aimed at understanding the limits and possibilities of the school dealing with pregnancy and the perception of oneself as pregnant student. The school seems to be a non place for bellies, once pregnancy of a young student points to a certain strangeness, even though invisible, between the young mother and the school.